Isolation of Lytic Bacteriophages infected Indonesian-strain Vibrio parahaemolyticus and its Protective Effects on Brine Shrimp (Artemia sp.) - Wahjuningrum, Dinamella; Ramhirez, Putri Shandra; Nuzullia, Laely; Yuhana, Munti; Sukenda, Sukenda; Nasrullah, Hasan (Faculty of Fisheries and Marine Universitas Airlangga, 2025)
Graphical Abstract Highlight Research vB_Vp_TSK01 and vB_Vp_JKT02 a specific parahaemolyticus bacteriophage were isolated from the shrimp aquaculture water. Compared to control vB_Vp_TSK01 reduced 11.46±1.35% of bacterial growth, and by 9.86±5.92% for vB_Vp_JKT02 treatment. Their cocktail had the highest parahemolyticus growth inhibition by 30.92±3.89%. The phage treatment increased the survival of the Artemia by 28.57% compared to infection control. Abstract Acute Hepatopancreatic Necrosis Disease (AHPND) caused by V. parahaemolyticus infection was one of the major diseases in shrimp culture in recent years. The Vibrio could also affect the survival of Artemia as the shrimp’s main live feed in the hatchery and they become the possible carrier for the AHPND. Phage therapy in shrimp aquaculture could reduce the application of the antibiotic as an antibacterial agent for the AHPND. The present study aimed to isolate the specific lytic phage for the Indonesian strain of V. parahaemolyticus (Vp) and evaluate the phage therapy for the brine shrimp Artemia infected with the Vp. The Vp-specific phage was isolated from the shrimp farm’s water at Tasikmalaya, and North Jakarta City, Indonesia. After isolation and plaque assay, brine shrimp were used as a model to evaluate the phages’ anti-Vibrio activity The Vp-lytic phage was successfully isolated from shrimp culture water at North Jakarta and Tasikmalaya (Vb_Vp_TSK01 and Vb_Vp_JKT01, respectively) and the results showed that both isolated phages and their cocktails were capable to inhibit the growth of Vp with the highest inhibition shown at the cocktail treatment (p<0.05). The survival of Artemia was higher in the phage treatments (p<0.005) compared to the infected control. Infected control had 68.33% of brine shrimp survival, and the Vb_Vp_TSK01, Vb_Vp_JKT01, and their cocktail had similar average brine shrimp survival of 91.11%. In conclusion, phage therapy proved effective in preventing vibriosis in brine shrimp under the conditions tested.